The Role of Local Luwu Culture in Creating Pluralistic Community Awareness - Yunus, Yunus; Khodijah, Khodijah (Scientia: Jurnal Hasil Penelitian, 2025)
This ethnographic study aims to deeply understand the role of local Luwu culture in forming and maintaining social cohesion in the multi-ethnic society of Sukamaju. Through a qualitative approach and data collection methods in the form of in-depth interviews with various informants, including academics (6 people), community leaders (6 people), and representatives from various dominant ethnic groups in Sukamaju, namely Toraja (4 people), Rongkong (4 people), Bugis (9 people), and students (8 people), this study explores the dynamics of social relations and cultural values ​​that contribute to the creation of harmony. The research findings show that the Sukamaju community, which is dominated by transmigration communities, is able to build harmonious multi-ethnic social relations. This success cannot be separated from the significant role of local Luwu culture with values ​​of wisdom such as Sipakatau (humanizing each other), Sipakalebbi (honoring each other), Sipakaingge' (reminding each other), and Sipakatou (loving each other). These values ​​are the basis for social interaction, bridging ethnic differences, and maintaining harmony. Furthermore, this study identified that the local wisdom of Tana Luwu is in line with the principles of pluralism that are developing in Indonesia, thus strengthening social integration at the local level. This study concludes that the internalization and practice of local Luwu cultural values ​​play a crucial role in creating and maintaining social cohesion in the multiethnic society of Sukamaju, providing important implications for understanding the development of social harmony in areas with high ethnic diversity.